Evaluation of microstructure, thermal, and mechanical properties of the green lignin‐based polyurethane/hydrophobic silica nanocomposite foam. Issue 7 (7th September 2020) - Mohammadpour, Raziye; Sadeghi, Gity Mir Mohamad
Abstract: In the present study, lignin‐based polyurethane foam (LPUF) and hydrophobic silica LPUF (SLPUF) were synthesized using different concentrations of silica nanoparticles (SNP). The effect of SNP on the structure and properties of SLPUF samples was investigated and compared with LPUF through the scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FT‐IR), thermogravimetric analysis (TGA), dynamic mechanical thermal analysis (DMTA), and compressive tests. The FT‐IR results showed changes in the H bonding interactions between the structures of SLPUF samples. Moreover, the SEM results indicated a decrease in the cell size of SLPUF samples. Incorporation of SNP improved the thermal stability of SLPUF samples while the compressive strength of SLPUF samples decreased in comparison with LPUF. Furthermore, the DMTA results revealed a decrease in the glass transition temperature from 90°C (LPUF) to around 52°C (SLPUF samples). This means that applying the hydrophobic SNP changes the foam type from a rigid foam to soft one. Therefore, significant changes were observed in the physical–chemical properties of the SLPUF samples compared to the LPUF. Abstract :